Plasticity in the Human Gut Microbiome Defies Evolutionary Constraints - Andres Gomez (American Society for Microbiology, 2019)
ABSTRACT The gut microbiome of primates, including humans, is reported to closely follow host evolutionary history, with gut microbiome composition being specific to the genetic background of its primate host. However, the comparative models used to date have mainly included a limited set of closely related primates. To further understand the forces that shape the primate gut microbiome, with reference to human populations, we expanded the comparative analysis of variation among gut microbiome compositions and their primate hosts, including 9 different primate species and 4 human groups characterized by a diverse set of subsistence patterns (n = 448 samples). The results show that the taxonomic composition of the human gut microbiome, at the genus level, exhibits increased compositional plasticity. Specifically, we show unexpected similarities between African Old World monkeys that rely on eclectic foraging and human populations engaging in nonindustrial subsistence patterns; these similarities transcend host phylogenetic constraints. Thus, instead of following evolutionary trends that would make their microbiomes more similar to that of conspecifics or more phylogenetically similar apes, gut microbiome composition in humans from nonindustrial populations resembles that of generalist cercopithecine monkeys. We also document that wild cercopithecine monkeys with eclectic diets and humans following nonindustrial subsistence patterns harbor high gut microbiome diversity that is not only higher than that seen in humans engaging in industrialized lifestyles but also higher compared to wild primates that typically consume fiber-rich diets. IMPORTANCE The results of this study indicate a discordance between gut microbiome composition and evolutionary history in primates, calling into question previous notions about host genetic control of the primate gut microbiome. Microbiome similarities between humans consuming nonindustrialized diets and monkeys characterized by subsisting on eclectic, omnivorous diets also raise questions about the ecological and nutritional drivers shaping the human gut microbiome. Moreover, a more detailed understanding of the factors associated with gut microbiome plasticity in primates offers a framework to understand why humans following industrialized lifestyles have deviated from states thought to reflect human evolutionary history. The results also provide perspectives for developing therapeutic dietary manipulations that can reset configurations of the gut microbiome to potentially improve human health.